Chemically activating MoS2 via spontaneous atomic palladium interfacial doping towards efficient hydrogen evolution - Zhaoyan Luo (Nature Portfolio, 2018)
While water reduction may provide a carbon-neutral means to produce hydrogen gas, there is a scarcity of efficient, earth-abundant electrocatalysts. Here, the authors add palladium into MoS2 materials to activate and stabilize the conductive basal plane to improve the electrocatalytic activity.